A Basic Semantic Common Level for Virtual Environments - Ibáñez-Martinez, Jesús; Delgado-Mata, Carlos (International Journal of Virtual Reality, 2006)
This paper describes our proposal for a new representation model for virtual worlds. Our model provides a layer of semantic information for virtual environments that does not intend to substitute application dependant approaches, but to constitute a common lower level for all of them. Our model is simple in that it consists of a reduced number of different elements and most of them can be automatically annotated. The paper shows the ideal annotation process. In this sense, we show our own experiences in annotating worlds. The model has already been successfully used in two different applications